Marine navigation and safety of sea transportation : STCW, maritime education and training (MET), human resources and crew manning, maritime policy, logistics and economic matters /: STCW, maritime education and training (MET), human resources and crew manning, maritime policy, logistics and economic matters. (©2013) - Unknown
No abstract available